Transthoracic management of liver dome hydatid cyst: a single-center experience in a North African country - Jedidi, Laila; Lahouel, Senda Ben; Attig, Yosr Ben; Mabrouk, Aymen; Cherni, Tarek; Moussa, Mounir Ben; Boudaya, Mohamed Sadok (Frontiers in Surgery, 2025)
BackgroundLiver dome hydatid cyst (LDC) presents a challenge for the surgeon and may be difficult to access through conventional laparotomy. Therefore, thoracic approach can be an effective alternative in these cases. This study aims to describe the postoperative outcomes of LDC operated via thoracotomy and to present the experience of one surgical center in Tunisia.Materials and methodsThis is a retrospective study including all patients with a diagnosis of liver dome hydatid cyst and underwent surgery via a posterolateral thoracotomy, in the Department of Surgery “A” of the Charles Nicolle Hospital between 2018 and 2023.ResultsForty-nine patients were included in our study. The mean age was 52 years with a standard deviation of 19. The male to female ratio was 0.96. The main presenting symptoms were right upper quadrant abdominal pain, right chest pain and cough. A posterolateral thoracotomy was indicated in four scenarios: right lung and liver dome cyst, liver dome cyst with thoracic rupture, recurrent liver dome cyst previously underwent surgery via a laparotomy and the accessibility of the cyst. The morbidity rate was 12.2%. Follow-up showed one recurrence.ConclusionPosterolateral thoracotomy appears to be a distinct and advantageous approach compared to traditional laparotomy, for the management of LDC, although the available evidence remains limited.